Local Wisdom Upacara Ngaben di Bali dan Keterkaitannya dengan Nilai-Nilai Bimbingan dan Konseling - Robbayani, Hamidah Bainina (Borobudur Counseling Review, 2022)
Local Wisdom or often called Local Wisdom is all forms of knowledge, belief, understanding, or insight as well as customs or ethics that guide human behavior in life in ecological communities (Keraf, 2002). Indonesia is the largest archipelagic country in the world consisting of 17,508 islands, both inhabited and uninhabited, crossed by the equator, located between the continents of Asia and Australia and between the Pacific Ocean and the Indian Ocean. A fairly wide area with a diversity of natural resources makes Indonesia have various ethnic groups, various beliefs, various customs, and various cultures which all combine into one, with the motto Bhineka Tunggal Ika (different but still one). The diverse cultures that affect the lives of Indonesian people, serve as guidelines for them. Each region has its own culture, has different policies and wisdom. Ngaben ceremony is one of the local wisdom in Bali. Where the Ngaben ceremony is a ceremony carried out for the burning of the bodies of Hindus in Bali. Ngaben ceremony is a ritual that is carried out to return the ancestral spirits to their original place. Ngaben in Balinese has a subtle connotation which is often called palebon. In local wisdom, this Ngaben ceremony can be related to the values of existing guidance and counseling. One of them is sincerity.